Tonny Njuguna of Shamba Shape Up talks about farming and climate change in East Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
The CGIAR Research Program on Climate Change Agriculture and Food Security (CCAFS) talked with Tonny Njuguna, presenter of the East African TV Show Shamba Shape-Up about the problems that farmers are facing, and how Shamba Shape-Up is helping them adapt to climate change. Learn more: ccafs.cgiar.org Facebook: cgiarclimate @cgiarclimate @cgiarclimate_EA www.shambashapeup.com Facebook: Shamba Shape UP @shambashapeup